The Charisma Machine: The Life, Death, and Legacy of One Laptop per Child by Morgan G. Ames (review). - Lövheim, Daniel (Technology & Culture, 2023)
Launched in 2005 and developed at the MIT Media Lab, the One Laptop per Child (OLPC) project built on the idea of giving all children across the Global South a computer of their own. Another important part of the OLPC's background was the hacker culture ethos of MIT, which from its early years had hailed passionate and playful attitudes to computers and programming. The first part of the book traces the intellectual roots of the OLPC back to the 1960s and another influential professor at MIT, Seymour Papert, who was among the first to express visions of one computer per child.